2021
DOI: 10.3389/fpubh.2021.754279
|View full text |Cite
|
Sign up to set email alerts
|

Combatting Substandard and Falsified Medicines: Public Awareness and Identification of Counterfeit Medications

Abstract: Objectives: The objective of this study was to determine the identification rate of substandard and falsified medications and its association with knowledge among public.Methods: This descriptive cross-sectional study was conducted in different geographic areas among a convenient sample of people aged 18 or older. A validated web-based electronic questionnaire was used for data collection tool. The questionnaire contained three sections assessing the following: (1) Sociodemographic data; (2) Knowledge regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…In terms of the ability to identify CFMs, the most identified physical attribute was the pattern on the packaging and placement of the printed details (mean = 3.378) (Table 5). This finding did not coincide with the studies conducted by El-Dahiyat et al [12], wherein the most identified label of information was found to be the manufacturing and expiration date. On the other hand, Phenylephrine HCl + Chlorpheniramine Maleate + Paracetamol was the most identified counterfeit over-the-counter (OTC) medicine (mean = 3.191) (Table 6), while Sildenafil citrate (mean = 3.195) was established as the most identified counterfeit prescription medicine (Table 7).…”
Section: Figure 1 Respondents' Sources Of Information Regarding Cfmscontrasting
confidence: 90%
“…In terms of the ability to identify CFMs, the most identified physical attribute was the pattern on the packaging and placement of the printed details (mean = 3.378) (Table 5). This finding did not coincide with the studies conducted by El-Dahiyat et al [12], wherein the most identified label of information was found to be the manufacturing and expiration date. On the other hand, Phenylephrine HCl + Chlorpheniramine Maleate + Paracetamol was the most identified counterfeit over-the-counter (OTC) medicine (mean = 3.191) (Table 6), while Sildenafil citrate (mean = 3.195) was established as the most identified counterfeit prescription medicine (Table 7).…”
Section: Figure 1 Respondents' Sources Of Information Regarding Cfmscontrasting
confidence: 90%
“…In addition to that, less than half (43.9%) of the study participants were able to tells, there was no penalty for supplying products without manufacture or entrance license. 27 This is deviated from the study conducted in Iran by Shahverdi et al (2012) majority of study participants (81.9%) were able to tell, there was no Penalty for supplying products without manufacture or entrance license. 20…”
Section: Discussionmentioning
confidence: 57%
“…In line with this study, a similar study reported by El-Dahiyat et al (2021) in United Arab Emirates revealed, only less than one -third of the participants were identified as counterfeit medications from the genuine medicine. 27 In Ethiopia, veterinary drug regulatory experts face a significant skills gap in veterinary drug regulatory activity and quality control. A study conducted by Zeru Hailu reveals that experts lack the ability to identify illegal veterinary drugs and have never attempted to distinguish between legal and illegal drugs in the market.…”
Section: Discussionmentioning
confidence: 99%
“…Providing education about these drug labeling standards would be a critical step in combating counterfeit products and limiting their use. 30 In our investigation, about half of the participants were able to tell the difference between a counterfeit and a genuine medicine. Large sections of the study participants were unfamiliar with the approach utilized to detect CFM when it came…”
Section: Discussionmentioning
confidence: 81%
“…Providing education about these drug labeling standards would be a critical step in combating counterfeit products and limiting their use. 30…”
Section: Discussionmentioning
confidence: 99%